A Novel Optimization Means of Transfer Efficiency for Resonance Coupled Wireless Power Transfer - Tan Linlin; Qiang Hao; Huang Xueliang; Cao Weijie; Sun Wenhui (Institute of Advanced Engineering and Science, 2013)
When the transmitting and receiving coils are equivalent with or not significantly smaller than their separation distance between the two coils, the results of numerical simulations for transfer efficiency of system show that the maximum coupling of two coils or maximum transfer efficiency occur with a certain tilt angle between two coils, which means the two coils with parallel on the same axis is not able to obtain the maximum transmission efficiency. In view of this feature of the wireless power transfer system, we propose a novel means to optimize the transfer efficiency by designing rotatable transmitting coils to achieve the appropriate tile angle. The experimental results show that the presented means is efficient and greatly improves the transfer efficiency. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2512